Impact of Occupational Stress on Emotional Intelligence and Its Components among Working Professionals in Kolkata - Dolly Sarkar, (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
The present study examines the impact of occupational stress on Emotional Intelligence (EI) and its three major components-Emotional Competency (EC), Emotional Sensitivity (ES), and Emotional Maturity (EM)-among working professionals in Kolkata, a fast-growing metropolitan hub of India. Using a cross-sectional quantitative design, data were collected from 320 employees (aged 21–58 years) across education, healthcare, banking, and information technology sectors through the Occupational Stress Index (Srivastava & Singh, 1984) and the Emotional Intelligence Scale (Singh & Chadha, 2006). Statistical analyses, including descriptive statistics, Pearson correlation, and hierarchical regression, revealed a significant negative relationship between occupational stress and total EI (r = −.43, p < .001). Occupational stress was found to strongly reduce Emotional Competency (β = −.35, p < .001) and Emotional Maturity (β = −.32, p < .001), while Emotional Sensitivity showed a comparatively smaller effect (β = −.19, p < .05). Overall, occupational stress accounted for 29% of the variance in total EI after controlling age, gender, and work experience. The study provides valuable insights into the field of organizational psychology by presenting empirical evidence from Kolkata, emphasizing that increasing occupational stress can significantly undermine emotional regulation, adaptability, and professional effectiveness among working individuals.
Keywords: Emotional Intelligence; Occupational Stress; Emotional Competency; Emotional Sensitivity; Emotional Maturity; Workplace Psychology; Kolkata